(3GdSeGA hGdYGde aj GddZIs - (3CHh YHO Gddg eMeO Hf GHGf Hf SYjO GddNej GdbQWHj,J (B354 (3g` s
(3ChdgG (B:s
(3HGH eG jbGd ai hSW GdEfSGf jbGd dhSW GdEfSGf (B: (3GdLgQI s
(3BNQgG (B:s
(3HGH LeGY VQhH eeG JYGdLg GdCYQGH ef GdCWYeI dGjSJYed gPG EdG ai TOI GdYjT jQGO Hg Cf GdeQCI dG JfGOi hdjOgG hdG JHGdi Hg dUYhHI MGdgG Je GdSaQ GdKGdK s
(3HChdgG JMHjS ddhRjQ CHj GdMSf GdhWGSi HJGQjN (B855s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B293s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs